2010
DOI: 10.1002/14651858.cd005427.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Combined chiropractic interventions for low-back pain

Abstract: Background Chiropractors commonly use a combination of interventions to treat people with low-back pain (LBP). Objectives To determine the effects of combined chiropractic interventions (that is, a combination of therapies, other than spinal manipulation alone) on pain, disability, back-related function, overall improvement, and patient satisfaction in adults with LBP, aged 18 and older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 66 publications
2
58
0
5
Order By: Relevance
“…[1][2][3] In addition to reducing pain, HVLA has been proposed to increase range of motion and produce neurologic changes to influence muscle relaxation, proprioception, and motor control. 4 Spinal manipulation is often accompanied with an audible pop or cavitation, but the importance of this noise to clinical effects has been disputed.…”
mentioning
confidence: 99%
“…[1][2][3] In addition to reducing pain, HVLA has been proposed to increase range of motion and produce neurologic changes to influence muscle relaxation, proprioception, and motor control. 4 Spinal manipulation is often accompanied with an audible pop or cavitation, but the importance of this noise to clinical effects has been disputed.…”
mentioning
confidence: 99%
“…In Table 9 we present quality ratings for the 20 articles included in this review that were evaluated for quality in one or more of 3 other reviews (Furlan et al, 2010;Walker et al, 2010). Overall, ratings for the majority of papers showed important gaps in quality markers for RCT study design, especially related to risk of bias, influence of co-intervention, and compliance with interventions.…”
Section: Resultsmentioning
confidence: 99%
“…However, we reviewed and combined quality ratings from 2 Cochrane and 1 Agency for Healthcare Research and Quality reviews (Furlan et al, 2010;Walker et al, 2010) for the studies included in this review.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Research demonstrates that spinal manipulation can have a positive impact on neck and low back pain. [53][54][55][56][57][58][59][60][61][62][63][64][65] Future directions to engage in after this study that researchers intend to pursue shall be to (1) engage in a larger study to confirm trends observed with this survey and monitor health care disparities in a more in-depth manner and (2) develop a demographic profile of non-Hispanic blacks that do not use chiropractic health care for comparison purposes.…”
Section: Discussionmentioning
confidence: 99%